Effect of Mouth Rinse of Chlorhxidine on The Occurrence of The Cariogenic Microorganisms - A. S. AI- Mizraqchi, A. S. AI- (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Twelve students rinsed their mouths once daily with ten ml. of 0.2 % aqueous solution of chlorhexidine gluconate for five days, and seven students served as a control group that used distilled water for rinsing. The result indicated that after one hour of treatment, an obvious sharp reduction in the viable counts of mutans streptococci, total aerobic bacteria, and to less extent the count of lactobacilli in saliva after one hr. of treatment. AnØ¢ increase in the number of these bacterial groups was clearly noticed three hrs. after the application of chlorhexidine and continued to increase later on. In spite of that increase, the bacterial numbers in saliva remained below the initial numbering in this study.